Next steps in development - above the neck - Collins, D.; MacNamara, A. (Talent development: A practitioner guide, 2018)
It is increasingly understood that psychological skills and characteristics have a significant impact on both performance and development. Termed Psychological Characteristics of Developing Excellence (PCDEs), these are the attitudes, behaviours and strategies which facilitate success across a wide range of achievement domains and enable individuals realise their potential both in their current domain and, if their interests change, in other domains. Simply, incorporating PCDEs into their talent development environment encourages young athletes to behave like champions. This chapter provides a step-by-step guide on how to operationalise PCDEs in your environment. The behaviours associated with PCDEs are outlined and examples of how these can be developed, deployed and refined in specific environments are provided. This chapter provides guidelines about how coach behaviors and coach systems can effectively promote the PCDEs underpinning effective development.